The governor and his subjects in the later Roman empire - Slootjes, Daniëlle. (Mnemosyne, Supplements, 2006)
This book presents new insights into the dynamics of the relationship between governors and provincial subjects in the Later Roman Empire, with a focus on the provincial perspective. Based on literary, legal, epigraphic and artistic materials the author deals with questions such as how provincials communicated their needs to governors, how they expressed both their favorable and critical opinions of governors' behavior, and how they rewarded 'good' governors. Provincial expectations, a continuous dialogue, interdependence, reciprocity, and ceremonial routine play key roles in this study that not only leads to a better understanding of Late Roman provincial administration, but also of the successful functioning of an empire as large as that of Rome.